2013
DOI: 10.1109/tvt.2012.2219566
|View full text |Cite
|
Sign up to set email alerts
|

Joint Cooperative-Transmit and Receive FDE for Single-Carrier Incremental Relaying

Abstract: Abstract-In this paper, we propose joint cooperativetransmit/receive frequency-domain equalization (cooperative-Tx/Rx FDE) with incremental relaying (IR) for broadband single-carrier (SC) transmission under the total and individual transmit power constraint at a source node (S) and a relay node (R). We derive the optimum cooperative-Tx/Rx FDE weights to minimize the mean square error (MSE) after packet combining at a destination node (D). We show that the optimum cooperative-Tx FDE weights allocate the transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Simulation results showed that the proposed ASCE methods with ZA-LMS/F and RZA-LMS/F algorithms achieve better performance than any sparse LMS method in point-to-point systems. In addition, the proposed method can also be applied in cooperative systems [15]. …”
Section: Regularization Parameter Selection For Sparse Lms/f Algormentioning
confidence: 99%
“…Simulation results showed that the proposed ASCE methods with ZA-LMS/F and RZA-LMS/F algorithms achieve better performance than any sparse LMS method in point-to-point systems. In addition, the proposed method can also be applied in cooperative systems [15]. …”
Section: Regularization Parameter Selection For Sparse Lms/f Algormentioning
confidence: 99%